QM/MM Molecular Dynamics Investigation of the Binding of Organic Phosphates to the 100 Diaspore Surface - Ganta, Prasanth B.; Kühn, Oliver; Ahmed, Ashour A. (Frontiers in Forests and Global Change, 2020)
The fate of phosphorus (P) in the eco-system is strongly affected by the interaction of phosphates with soil components and especially reactive soil mineral surfaces. As a consequence, P immobilization could occur which eventually leads to P inefficiency and thus unavailability to plants with strong implications on the global food system. A molecular level understanding of the mechanisms of the P binding to soil mineral surfaces could be a key for the development of novel strategies for more efficient P application. Much experimental work has been done to understand P binding to several reactive and abundant minerals especially goethite (a-FeOOH). On the other hand, atomistic modeling of the P-mineral molecular systems using molecular dynamics (MD) simulations is emerging as a new tool which provides more detailed information regarding the mechanisms, nature, and strength of these binding processes. The present study characterize the binding of the most abundant organic phosphates in forest soils, inositol hexaphosphate (IHP) and glycerolphosphate (GP), to the 100 diaspore (a-AlOOH) surface plane. Here, different molecular models have been introduced to simulate typical situations for the P-binding at the diaspore/water interface. For all models, quantum mechanics/molecular mechanics (QM/MM) based MD simulations have been performed to explore the diaspore–IHP/GP–water interactions. The results provide evidence for the formation of monodentate (M) and bidentate (B) motifs for GP and M and as well as two monodentate (2M) motifs for IHP with the surface. The calculated interaction energies suggest that GP and IHP prefer to form the B and 2M motif, respectively. Moreover, IHP exhibited stronger binding than GP with diaspore and water. Further, the role of water in controlling binding strengths via promoting of specific binding motifs, formation of H-bonds, adsorption and dissociation at the surface, as well as proton transfer processes is demonstrated. Finally, the P-binding at the 100 diaspore surface plane is weaker than that at the 010 plane highlighting the influential role of the coordination number of Al atoms at the top surface of diaspore.